2008
DOI: 10.1016/j.jtcvs.2007.11.072
|View full text |Cite
|
Sign up to set email alerts
|

Is aortic wall degeneration related to bicuspid aortic valve anatomy in patients with valvular disease?

Abstract: In diseased bicuspid aortic valves, there was a statistically significant association between type A valve anatomy and a more severe degree of wall degeneration in the ascending aorta and dilatation of the aortic root at younger age compared with type B valve anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
2
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 18 publications
4
91
2
6
Order By: Relevance
“…In humans, most BAVs result from fusion of either the right-coronary and left-coronary leaflets (R-L) or the right-coronary and noncoronary leaflet (R-N). R-N BAV is associated with a greater degree of valve dysfunction, and it has also become clear over the years that BAV morphology is of prognostic relevance in the management of patients with BAVs (43)(44)(45). Work in animal models suggests that the 2 subtypes may be distinct etiological entities; R-N BAVs would result from defective development of the cardiac OFT endocardial cushions, whereas R-L BAVs result from an extra fusion of the septal and parietal ridges (38).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, most BAVs result from fusion of either the right-coronary and left-coronary leaflets (R-L) or the right-coronary and noncoronary leaflet (R-N). R-N BAV is associated with a greater degree of valve dysfunction, and it has also become clear over the years that BAV morphology is of prognostic relevance in the management of patients with BAVs (43)(44)(45). Work in animal models suggests that the 2 subtypes may be distinct etiological entities; R-N BAVs would result from defective development of the cardiac OFT endocardial cushions, whereas R-L BAVs result from an extra fusion of the septal and parietal ridges (38).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BAV patients with fusion of the left coronary and right coronary cusps were significantly younger at the time of surgery and had a significantly larger aortic root diameter versus BAV patients with fusion of the right coronary and non-coronary cusps. The investigators of this study concluded that the presence of more severe histopathological changes at a younger age, and a significantly larger aortic root diameter in BAV patients with fusion of the left coronary and right coronary cusps, may be predictive of a more accelerated and "malignant" BAV phenotype (Russo et al, 2007).…”
Section: Different Cusps Fusion Patterns In Bav Diseasementioning
confidence: 80%
“…There is emerging evidence from the recent literature that the different cusp fusion patterns in BAV disease are associated with specific lesions of the proximal aorta. The histopathological grading of the of aortic wall changes in patients who underwent surgery for BAV disease demonstrated a more severe degree of wall degeneration in the ascending aorta in patients with fusion of the left coronary and right coronary cusps versus fusion of the right coronary and non-coronary cusps (Russo et al, 2007). The prevalence of fibrosis, cystic medial necrosis, elastic fragmentation, and inflammation has been shown to be significantly higher in patients with fusion of the left coronary and right coronary cusps.…”
Section: Different Cusps Fusion Patterns In Bav Diseasementioning
confidence: 97%
“…There is a release of matrix metalloproteinases (MMPs), injury to the ECM including elastin fragmentation, cell death and in consequence the loss of support and flexibility of the aortic wall. These changes in the middle layer of the aortic wall lead to the development and expansion of the aortic aneurysm [1,4,11]. The incidence of TAAD in patients with BAV is estimated at about 30-40%, so it is three times higher than in patients with tricuspid valve, in which it is about 12% [1,3].…”
Section: Discussionmentioning
confidence: 99%